Electrical Properties of Cobalt Oxide/Silica Nanocomposites Obtained by Sol-Gel Technique - Ali, Gomaa A. M.; Fouad, Osama A.; Makhlouf, Salah A. (Science Publications, 2016)
This work is an extension of our previous studies on cobalt oxide nanoparticles impeded in a silica matrix. Here we study the preparation and characterization of high cobalt content materials (60-90 wt%). In addition, the DC electrical conductivity of the prepared materials in a wide temperature range (350-673 K) was measured and discussed. The activation energy has been obtained according to Mott’s Small-Polaron Hopping (SPH) and Mott’s and Greaves Variable Range Hopping (VRH) models.